Theology and poetry : studies in the medieval piyyut - Petuchowski, Jakob Josef, 1925-1991 (Littman library of Jewish civilization (Series), 2004)
In the Middle Ages, unconventional theological views were often expressed in poetic form. Jakob Petuchowski provides parallel texts of ten medieval theological poems in the standard liturgy that express unconventional and daring theological ideas, each with a commentary on the poem and its author, and a survey of Jewish thought on its particular theme.